Wildlife culling as a biophobic response to zoonotic disease risk: why we need a one health approach to risk communication - Anderson, C. Jane; Reaser, Jamie K. (Frontiers in Conservation Science, 2024)
Zoonoses – infectious diseases that are transmitted between people and other animals – are one of the foremost public health threats. Public health messaging is a critical tool for informing at-risk communities about zoonotic disease threats and effective mitigation measures. Unfortunately, when not carefully crafted, public health messaging can foster fear-based (biophobic) responses to wildlife that may carry zoonotic pathogens—enculturating fear, disgust, and other forms of aversion. In worst case scenarios, biophobia of zoonotic hosts can result in humans culling wildlife populations or destroying their habitat. To better understand how public health messaging can responsibly provide necessary information on zoonoses risks while also promoting an affinity (biophilia) for potential zoonotic pathogen hosts, we conducted a literature review to identify cases of zoonoses-initiated wildlife culls and evaluated patterns and trends. We found that culls are frequently of native wildlife species, rather than nonnative species, and often increase threats to human health rather than mitigate them. We further found that the cultural impetus behind culls is rarely evaluated or discussed in the literature. Clearly, more research is needed in this regard. Human, animal, and environmental health are intertwined, and thus zoonoses prevention and mitigation is best addressed through a One Health lens. There is a need for public health and conservation professionals to collaborate in the development of risk mitigation messaging that enculturates effective zoonoses preventative measures, including biodiversity conservation.